2021
DOI: 10.1161/circresaha.121.319828
|View full text |Cite
|
Sign up to set email alerts
|

PDE1 Inhibition Modulates Ca v 1.2 Channel to Stimulate Cardiomyocyte Contraction

Abstract: Rationale: Cyclic adenosine monophosphate (cAMP) activation of protein kinase A (PKA) stimulates excitation-contraction coupling, increasing cardiac contractility. This is clinically achieved by beta-adrenergic receptor stimulation (b-ARs) or inhibition of phosphodiesterase type-3 (PDE3i), though both approaches are limited by arrhythmia and chronic myocardial toxicity. Phosphodiesterase type-1 inhibition (PDE1i) also augments cAMP and enhances contractility in intact dogs and rabbits. Unlike b-ARs… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 54 publications
0
10
1
Order By: Relevance
“…Interestingly, in healthy dogs and rabbits and in those with HF, a newly developed PDE1 inhibitor, ITI-214, produces acute inotropic and lusitropic effects as well as arterial vasodilation by promoting a cAMP pool independent of β-AR signalling, specifically emanating from A2R 130 . In guinea pig cardiomyocytes, ITI-214 (with a low dose of the adenylate cyclase stimulator, forskolin) stimulated contractility, mainly by enhancing ICa,L, with little effect on Ca 2+ transients and myofilament protein phosphorylation, in contrast with β-AR stimulation or PDE3 inhibition 131 . These findings prompted the first clinical trial of ITI-214 in humans with HF 132 .…”
Section: [H1] Pdes In Cardiac Hypertrophy and Hfmentioning
confidence: 99%
“…Interestingly, in healthy dogs and rabbits and in those with HF, a newly developed PDE1 inhibitor, ITI-214, produces acute inotropic and lusitropic effects as well as arterial vasodilation by promoting a cAMP pool independent of β-AR signalling, specifically emanating from A2R 130 . In guinea pig cardiomyocytes, ITI-214 (with a low dose of the adenylate cyclase stimulator, forskolin) stimulated contractility, mainly by enhancing ICa,L, with little effect on Ca 2+ transients and myofilament protein phosphorylation, in contrast with β-AR stimulation or PDE3 inhibition 131 . These findings prompted the first clinical trial of ITI-214 in humans with HF 132 .…”
Section: [H1] Pdes In Cardiac Hypertrophy and Hfmentioning
confidence: 99%
“…Recently, the group of David Kass has shown the role of PDE1C in rabbit and dog hearts, which, similar to human hearts, express predominantly this isoform and show positive inotropic and chronotropic effects after inhibiting PDE1. These effects are due to PDE1C activity over a soluble AC-cAMP nanodomain that regulates LTCC current via PKA, but does not involve modulation of SERCA current, phosphorylation of PLB, TnI, and myosin binding protein C, like in the β-AR-mediated contractility [119,121].…”
Section: Pde1mentioning
confidence: 99%
“…A possible explanation for the observed increased contractility was reported by Muller et al . [ 61 ], who demonstrated that the L-type calcium current, the trigger to calcium-sensitive calcium release, is potentiated by PDE1 inhibition. Interestingly, the study found only relatively small changes at PKA activity sites distal to L-type channels, such as PLB or the contractile machinery, indicating the importance of PDE1 in local control of cAMP.…”
Section: Phosphodiesterasesmentioning
confidence: 99%
“…At the same time, PDE3 inhibition was reported to lead to a substantial increase in L-type calcium current in human atrial cells [ 70 ]. In the ventricles of guinea pigs, PDE3A was shown to regulate the cAMP pool associated with the regulation of L-type calcium current [ 61 , 71 ], and this interaction was also suggested in one study using mouse cells [ 72 ], although this finding was not confirmed in another study [ 67 ]. The other type of PDE3, PDE3B, is localized preferentially in the t-tubules, close to dyads and mitochondria, and is thought to partly mediate the myocardial damage during ischaemia-reperfusion and probably contributes to the regulation of cellular metabolism [ 73 ].…”
Section: Phosphodiesterasesmentioning
confidence: 99%